The illusionist - Burger, Neil.; Norton, Edward; Giamatti, Paul.; Biel, Jessica, 1982-; Sewell, Rufus, 1967-; Marsan, Eddie; Wood, Jake.; Fisher, Tom.; Pope, Dick, B.S.C.; Geraghty, Naomi; Glass, Philip; Millhauser, Steven; et al. (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2006)
The acclaimed illusionist Eisenheim has not only captured the imaginations of all of Vienna, but also the interest of the ambitious Crown Prince Leopold. When Leopold's new fiancee rekindles a childhood fascination with Eisenheim, the Prince's interest evolves into obsession. Suddenly the city's Chief Inspector finds himself investigating a shocking crime. But even as the Inspector engages him in a dramatic challenge of wills, Eisenheim prepares for the most impressive illusion yet.
Based on the short story "Eisenheim, the illusionist" by Steven Millhauser.
DVD release of the 2006 motion picture.
Special features: commentary by writer/director Neil Burger ; The making-of 'The illusionist' featurette ; Jessica Biel on 'The illusionist' featurette ; trailer.
Director of photography, Dick Pope ; editor, Naomi Geraghty ; music, Philip Glass ; costume designer, Ngila Dickson ; production designer, Ondrej Nekvasil.
Edward Norton, Paul Giamatti, Jessica Biel, Rufus Sewell, Eddie Marsan, Jake Wood, Tom Fisher.
MPAA rating: PG-13; for some sexuality and violence.
Keywords: Magicians -- Austria -- Vienna -- Drama; Hallucinations and illusions -- Austria -- Vienna -- Drama; Magic tricks -- Austria -- Vienna -- Drama; Criminal behavior -- Austria -- Vienna -- Drama; Criminal investigation -- Austria -- Vienna -- Drama; Magia -- Austria -- Viena -- Teatro; Alucinaciones e Ilusiones -- Austria -- Viena -- Teatro; Magicians -- Austria -- Vienna -- Drama; Criminal behavior; Criminal investigation; Hallucinations and illusions; Magic tricks; Magicians; Vienna (Austria) -- Drama; Austria -- Vienna; Feature films; Thrillers (Motion pictures, television, etc.); Detective and mystery films; Thrilller -- Feature; Mystery -- Feature; Romance -- Feature; Crime -- Feature; Feature films; Suspense films; Mystery films; Love stories; Detective and mystery films; Drama; Feature films